Chemically Fueled Autonomous Responsiveness of Spherical Polyelectrolyte Brushes - Liu, Liqun (Langmuir : the ACS journal of surfaces and colloids, 2025)
Stimuli-responsive spherical polyelectrolyte brushes (SPBs) have been of great interest for many enticing applications, yet their responsive functions are usually realized at the equilibrium state upon manually switching the external pH value or ionic strength, showing limited autonomous behaviors. Herein, we report on SPBs bearing autonomous responsive behaviors enabled by a chemically fueled reaction network. SPBs comprising poly(acrylic acid) (PAA) brush layers are employed. Upon the addition of carbodiimide (EDC) as a chemical fuel, the hydrophilic carboxylic acids in PAA chains are converted to hydrophobic anhydrides in aqueous media, thus resulting in the collapse of the brush layers. However, with the depletion of EDC, the formed anhydrides undergo spontaneous hydrolysis to the initial carboxylic acids, resulting in the autonomous recovery of the initial stretching state. Such a collapse-stretching evolution process is highly autonomous, distinctly differing from the conventional signal-switching modes. The lifetime of the evolution process can be controlled by adjusting the concentration of EDC, and repetitive fueling can lead to cyclic evolution. As a conceptual application, SPBs are employed as a smart adsorbent for the removal of organic dyes. This work may contribute to the development of adaptive SPBs for many competitive applications varying from drug delivery to water treatment